Os fornos artesanais de cal de Pataias (Alcobaça): resultados preliminares do seu estudo: DOI: https://doi.org/10.5281/zenodo.7920571 - Inácio, Tiago (Estudos Arqueológicos de Oeiras, 2023)
With 31 specimens, Pataias lime kilns are currently the largest group of artisanal lime kilns in portuguese territory. Considering the importance of this heritage at a national level, in january of 2018 the author, with the direct support of UFPM, began to, exhaustively and exclusively, investigate the lime kilns of Pataias in their most varied aspects. Since that date, the author has carried out exhaustive fieldwork, surveying documents in the most diverse archives, thematic visits, interviews, surveying and collecting tools, excavations, cleaning, exhibitions, survey and inventory of tile panels alluding to the lime industry of Pataias, participation in congresses and scientific meetings. This investigation resulted in the Master’s thesis entitled “The artisanal lime kilns of Pataias: history, memory and progress”, defended in march of 2022 at Universidade Aberta. In this brief article will be presented some of the results obtained from the investigation.